"The feedback dilemma"-provider and learner perspectives regarding the barriers and facilitators for giving and receiving feedback in medical education: A parallel mixed methods approach - Yamini Pusdekar; Vinod Pusdekar; Akanksha Dani; Ajeet Saoji; Madhur Gupta (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Learning in medical education involves a multitude of practical tasks and skills that are amenable to feedback provision. Though passive feedback is given, there is a consistent gap in feedback provision and its receipt. This study aims to assess provider perspectives on feedback and learner attributes influencing the receipt of feedback in medical educational settings. MATERIALS AND METHODS: A parallel mixed methods study was conducted in September 2023 at a tertiary care teaching institute. A convenience sample of 40 medical teachers comprising two faculties per department and 30 students were included. Focus group discussions (FGDs) were conducted with students from each academic year for assessing the student-level factors (facilitators and barriers) in the receipt of feedback. RESULTS: Among the 40 medical teachers who were interviewed, the majority of 23 (57.5%) were assistant professors and nearly half of them (18; 45.0%) were below the age of 30 years. The majority of the respondents (28; 70.0%) were females, and 34 (85.0%) of them were postgraduates. Most of them (24; 60.0%) had worked for more than 10 years at the institute. It was observed that 80.0% of the respondents had given feedback to their students at some point in their careers. The major barriers for providing feedback were lack of curricular guidelines, fear of affective responses from students, burden of clinical, administrative work, and lack of perceived need by both students and teachers. DESTEP analysis of the student-level factors governing the receipt of feedback shows the effects of institutional ethics and culture, feedback model utilized, and the influence of learner behaviors, motivations, and teacher attributes. CONCLUSION: The study elucidates mentor- and mentee-level influencers for providing and receiving feedback. Effective teacher-student partnerships along with an optimal skill set are required to recognize the need, opportunities, and processes to provide and seek feedback. Shifting the focus from feedback giving to active feedback seeking would be a step toward creating effective and pragmatic feedback systems.